Benefits of Cyber-Physical Systems Modeling and Simulation with LabView - Szász, Csaba (Recent Innovations in Mechatronics, 2021)
Cyber-physical systems (CPSs) as part of the Industry 4.0 strategy, represents one of the most challenging research topic for engineers. It’s well known that CPSs integrate at highest level digital technology (computation, control and networking) into physical objects. However, by incorporating various heterogeneous subsystems with different energy levels and functionalities, both analogue and digital signals management, as well as a large scale of communication and information technologies, their modeling and simulation becomes a difficult engineering task. In the past years a huge number of research papers has been dedicated to identify and develop modeling techniques and simulation toolkits being able to handle CPSs complexity. Following these trends, this paper is focused to research and evidence issues linked with the LabView graphically oriented programming technology utilization for CPSs modelling and simulation purposes. Both advantages and shortcomings of this very special technology are studied in order to design and implement a viable software framework being able to model and simulate various CPS structures. As a concrete example, a specific CPS configuration consist of six computer-based mechatronic systems that constitute a laboratory-prototype manufacturing plant has been chosen for LabView-based modeling and simulation. Various virtual instrument-type models of this setup has been conceived and proposed for real-time simulation. It has been concluded then that the application of LabView technology lead to interesting and useful results. The paper specially highlights the benefits and versatility of LabView utilization for complex CPSs modeling and simulation purposes.